APPLICATION OF THE GUIDED INQUIRY LEARNING MODEL TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS IN NATURAL SCIENCE SUBJECTS - Nur Efendi; Dinda Tia Tinara; Sabrina Oktavia Irawati; Nabila Indana Zulfa (P3I UMSurabaya, 2024)
This research aims to improve students' critical thinking skills through the application of guided inquiry learning. This research is Classroom Action Research which was carried out in two cycles. Each cycle consists of four stages: planning, acting, observing, and reflecting. The research subjects were class VII ECP students at SMP Muhammadiyah 1 Sidoarjo for the 2024/2025 academic year, totaling 34 students and consisting of 18 men and 16 women. The data collection techniques used in this research were essays, tests, observations and interviews, with data validation using triangulation techniques. The essay test used in this research contains six aspects of critical thinking skills: interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data were analyzed using qualitative descriptive techniques. The spiral model is used for research procedures. The research results show that every aspect of critical thinking ability increases in two guided inquiry cycles of learning implementation. Interpretation increased 30.30%; analysis 36.36%; evaluation 41.67%; inference 31.82%; explanation 37.88%; and self-regulation 24.25%. Based on the results of data analysis, it can be concluded that the implementation of guided inquiry learning is able to increase the critical thinking abilities of class VII ECP students at Muhammadiyah 1 SIdoarjo Middle School for the 2024/2025 academic year.